A Survey of Suctioning Practices among Physical Therapists, Respiratory Therapists and Nurses. Issue 6 (3rd December 1999) - Brooks, Dina; Solway, Sherra; Graham, Ian; Downes, Laurie; Carter, Margaret
Abstract : OBJECTIVE: To assess the current tracheal and oropharyngeal suctioning practice variability within and among the professions of physical therapy, respiratory therapy and nursing. DESIGN: A mail survey of physical therapists, respiratory therapists and registered nurses who perform suctioning. The survey instrument consisted of questions about professional characteristics, clinical suctioning practice and sociodemographics. SETTING: The survey was restricted to professionals practising within the province of Ontario. PARTICIPANTS: Random samples (n=448) were drawn from membership of the regulatory boards of all three professions. MAIN RESULTS: Fifty-eight per cent of respondents returned completed questionnaires. There was large variation in reports of gloving procedure (eg, double clean: 26% for physical therapists, 5% for respiratory therapists, 55% for registered nurses, P<0.0001) and technique of catheter use (sterile, inline or clean, P<0.01). There was also discrepancy in the techniques used to minimize harmful effects, ie, prelubrication with gel (83% for physical therapists, 54% for respiratory therapists, 17% for registered nurses, P<0.0001), use of hyperinflation (12% of physical therapists, 25% of respiratory therapists, 39% of registered nurses never hyperinflate) and use of instillation (7% of physical therapists, 0% of respiratory therapists, 19% of registered nurses never instill). However, there was agreement about the routine application of hyperoxygenation (74% or more) and there was almost perfect agreement (99% or more) within and across the three professions that secretion removal was the main indication for suctioning. CONCLUSIONS: The results of this study indicate a wide variation in suctioning techniques among physical therapists, respiratory therapists and registered nurses. Comparisons among professions revealed inconsistencies in some areas, such as the use of in-line catheters, gloving procedures, prelubrication and hyperinflation.